MEKANISME TRANSMISI GONCANGAN HARGA MINYAK DAN HARGA PANGAN DUNIA TERHADAP PEREKONOMIAN MAKRO INDONESIA: PENDEKATAN STRUCTURAL VECTOR AUTOREGRESSIVE (SVAR) - Abdul Khaliq (Business Management Journal, 2017)
This study examines the transmission channels of oil and food price shocks to selected Indonesian macroeconomic variables including Indonesia industrial production index, world interest rate, inflation, domestic interest rate, real effective exchange rate, and Jakarta Composite Index using monthly data over the period 2001M01-2013M08. An empirical analysis is carried out by utilizing structural vector autoregressive (SVAR) framework. Impulse response functions (IRFs) and forecast variance decompositions (FEVDs) are employed to track the impact of oil and food price shock to Indonesian economy. The empirical findings of IRFs suggest that oil price shock negatively affects industrial production, depreciates real effective exchange rate, increases inflation and interest rate, and negatively affects aset price. However, following food price shocks, industrial production increases, depreciates real effective exchange rate, increase stock return. Moreover, inflation and interest rate respond positively following food price shocks. The FEVDs results clearly reveals that the variation in industrial production growth, inflation, interest rate, real effective exchange rate, and aset price due to oil price shock is relatively larger than the food price shocks. This implies that oil price is most important source of disturbances in Indonesian macroeconomy. As a whole, this study recommend that world oil and food price should be considered for policy analysis and forecasting an Indonesian macroeconomy.Key Words : Oil and food price shocks, SVAR, IRFs, FEVDs, Indonesia